Reply to "Re-evaluating the evidence for facilitation of stickleback speciation by admixture in the Lake Constance basin" - Berner, Daniel (2021)
A Matters Arising article1 raised concerns about the interpretation of our findings reported in our recent publication on admixture-facilitated ecological speciation in Lake Constance stickleback2. After careful consideration of the criticism, including additional analyses testing the proposed alternative hypotheses, we can confirm our confidence in the inference of secondary contact between a West European and an East European stickleback lineage in the catchment of Lake Constance, and that this admixture facilitated the ecological divergence between lake and stream ecotypes within Lake Constance2. In particular, Berner1 (i) questioned whether West and East European stickleback populations should be considered as divergent lineages, (ii) suggested that Lake Constance stickleback originated from the upper Danube instead of East Europe, (iii) questioned the suitability of our demographic modelling approach to reject an ‘ecological vicariance’ scenario, (iv) proposed that divergent selection within Lake Constance biased our inference of a secondary contact and admixture scenario, and (v) criticized our conclusion on admixture-facilitation of ecological speciation as premature. We address each of these concerns in this sequence.